(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The subject of research in this paper is the use of agricultural products in powder form by drying them with solar energy, taking into account the loss of productivity of some types of agricultural products in the conditions of Kyrgyzstan. The purpose of this work is to study the results of a study of the influence of the nature of the movement of a heat storage device on the speed of drying products. As a result of the experimental method, the influence of one-way and two-way movement of the refrigerator in the drying chamber on the drying rate of products was studied. It should be noted that at the observed cooling water velocities in «hot box» devices, including radiative-convective solar dryers, a laminar flow regime with natural movement of the coolant (0.1-0.4 m/s) is realized with). The results of drying tomatoes and carrots, radishes and pumpkins in a drying chamber with one-way and two-way movement of a heat storage device are given. Based on the research results, the following conclusions can be drawn: it is necessary not only to ensure high rates of moisture evaporation from agricultural products, but also to ensure quick and timely removal of moisture from the drying chamber. Otherwise, the evaporation potential will decrease, which is expressed as the difference in partial pressures of water vapor on the surface of the product and in the environment (in this case, the volume of the drying chamber). The originality and scientific value of the results obtained in the course of the study was determined by the dependence of the regularities of the process of drying liquid viscous agricultural products on the type and physical characteristics of the products, solar radiation and the environment. The practical significance of the developed solar dryers lies in the fact that they allow drying agricultural products in a liquid-viscous state to a lower humidity and obtaining powder from the products. The introduction of the obtained research results into production in the future will help create new jobs and revive the economy of the regions.